'When I don't have money to buy the drugs, I just manage.'—Exploring the lived experience of persons with physical disabilities in accessing primary health care services in rural Ghana. (October 2018) - Dassah, Ebenezer; Aldersey, Heather M.; McColl, Mary Ann; Davison, Colleen
Abstract: The United Nations Convention on the Rights of Persons with Disabilities recognizes the rights of persons with disabilities' access to health care, including primary health care (PHC). However, growing evidence indicates that individuals in rural areas generally experience health access issues, and these issues are even worse for those with physical disabilities. Knowledge about such experiences is critical for policy design and clinical practice to promote PHC access for persons with physical disabilities in rural areas. This study seeks to explore the experiences of persons with physical disabilities in accessing PHC services in the predominantly rural Upper West Region of Ghana. We conducted semi-structured interviews with 18 participants living with physical disabilities, and used both deductive and inductive approaches to analyze the data. Participants shared experiences at three broad levels: the health system level, individual level and health-seeking behaviors level. Within the health system level, we identified three main categories: service availability (presence of health facilities, deficient drug supply and lack of providers), acceptability (positive and negative attitudes of providers and perceived high and low quality of care) and accommodation (inaccessible health facilities and equipment). The experiences at the individual level included financial constraints and mobility to health care facilities. Health-seeking behaviors related to how the individual reacted and responded to access barriers, which included searching for traditional healing, resorting to self-medication, making sacrifices in managing their conditions and relying on spiritual means. The information provided in this study is potentially important to policy makers and PHC providers as it presents evidence on the barriers and facilitators to PHC access in a rural setting. In particular, understanding individuals' experiences and how they develop health-seeking behaviors to overcome access barriers will be critical for policy design and client-centered service delivery in rural Ghana and potentially other low- and middle-income countries. Highlights: Persons with physical disabilities face barriers in accessing primary health care. Barriers occur at both the individual and health care system levels of scale. Clients develop different health-seeking behaviors to overcome access barriers.